Critoniopsis hermogenesii (Vernonieae, Asteraceae), a new endemic species from Serra do Mar Mountain Range, São Paulo state, Brazil - Monge, Marcelo; Volet, Danilo Poso; Semir, João (Phytotaxa, 2019)
A new species of Critoniopsis from São Paulo state in Brazil is described from São Luis do Paraitinga and Cunha and is an endemic of the Atlantic Forest in the Serra do Mar Mountain Range. The new species is differentiated from the other Brazilian species of the genus by its habit, colour of the glandular trichomes on leaves, venation, size of inflorescences, and colour of involucral bracts. The new species is considered critically endangered according to the IUCN Red List guidelines. We also conducted a micromorphological analysis of vegetative and reproductive organs using scanning electron micrography.